Characteristics of white coat hypertension in Chinese Han patients with type 2 diabetes mellitus. (August 2014) - Zhou, Jianguang; Liu, Changyun; Shan, Peijia; Zhou, Yingqi; Xu, Erli; Ji, Yufeng
Abstract Objectives: This study documented the prevalence and clinical features of white coat hypertension (WCH) among Chinese Han patients with type 2 diabetes mellitus (T2DM). Methods: Clinic and ambulatory blood pressure (BP) measurements were compared in 856 patients with T2DM to determine the frequency of WCH (WCH was defined as clinical blood pressure ≥140/90 mmHg and daytime blood pressure <135/85 mmHg and/or 24-h ambulatory BP (ABP) mean value of <130/80 mmHg on ambulatory BP monitoring (ABPM). Weight, waist circumference (WC), body mass index (BMI), waist to height ratio (WHtR), fasting blood glucose, glycosylated hemoglobin level and circadian BP patterns were also measured to find clinical features predictive of WCH in T2DM. Results: The prevalence of WCH was 7.36% (63/856) in the overall population, 6.13% (29/473) in male and 8.88% (34/383) in female (p < 0.05). WCH accounted for 14.03% (63/449) of diagnosed hypertension. Age, course of T2DM, male WC were independent protective factors, whereas female sex, smoking and alcohol consumption were independent risk factors for WCH in T2DM. Non-dippers and reverse dippers made up larger proportion of the WCH group (p < 0.01). Conclusion: WCH is relatively common among T2DM patients, it is a unique condition distinct from essential hypertension (EH), and WCH patients also exhibit significant differences in clinical parameters.